(untitled) (The Pakistan Development Review, 2023)
Financial inclusion of firms is crucial to create jobs, boost economic growth, and promote sustainable development. The study examines how financial inclusion affects enterprise export performance based on access to finance ratios. The study analyses the effects of firms’ financial inclusion determinants and macro environment factors on firms’ export values. The data comes from Pakistan’s manufacturing sector covering 400 firms listed on Pakistan Stock Exchange from 1999-2021. Driven by the nature of the data, the Method of Moment Quantile Regression is employed to assess the below and above mean regression estimations, and a two-step system GMM approach is used to address endogeneity concerns. The results of the study are robust against different specifications. The study reveals that assets positively impact a firm’s export performance, emphasising the importance of asset investment for foreign market competition. Asset tangibility negatively impacts export performance, except for low-gearing corporations, and fixed assets dominate. A balanced asset mix is crucial for improving exports. Debt-to-equity ratios, except for high-gearing firms, boost export performance, but domestic firms with high leverage ratios are more likely to fail. To avoid excessive leverage risks, firms must balance debt and equity. Diversifying the asset mix to include liquid and intellectual property can boost export success. Gearing affects export performance differently depending on a firm’s debt levels. Low-geared enterprises can leverage assets and debt to boost exports, while high-geared enterprises may be financially constrained and face challenges from excessive debt. Therefore, enterprises must carefully examine their gearing levels and make informed decisions on optimising their asset composition for optimal export performance. The study also opens up the possibility of further research on the role of exchange rates and firms’ investment in line with export performance.